The Splinternet - Lemley, Mark A. (Revista Amagis Jurídica, 2024)
SUMMARY. 1 Your parents’ internet. 2 The splintering of the internet. 2.a Nationalizing software and regulation. 2.b National hardware networks. 2.c        Nationalizing the network itself. 3 The internet is worth saving. 4 What can we do? 5 Conclusion. References.